2021
DOI: 10.1021/acs.analchem.0c04497
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Automated Diagnosis and Risk Assessment through Metabolomics and Machine Learning

Abstract: COVID-19 is still placing a heavy health and financial burden worldwide. Impairment in patient screening and risk management plays a fundamental role on how governments and authorities are directing resources, planning reopening, as well as sanitary countermeasures, especially in regions where poverty is a major component in the equation. An efficient diagnostic method must be highly accurate, while having a cost-effective profile. We combined a machine learning-based algorithm with mass spectrometry to create… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 31 publications
6
66
0
Order By: Relevance
“…22 Yet, a recent study by Delafiori et al reported decreased abundances of lysoPC species in the serum of COVID-19 positive patients. 33 Across both classifiers, PE 50:9 was selected as indicative of COVID-19 with the highest weight toward the disease, while other PE species such as PE 34:2 was selected as indicative of being negative for COVID-19. Increased abundance of PE species was also recently reported by Ford et al in nasal swabs from COVID-19 positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…22 Yet, a recent study by Delafiori et al reported decreased abundances of lysoPC species in the serum of COVID-19 positive patients. 33 Across both classifiers, PE 50:9 was selected as indicative of COVID-19 with the highest weight toward the disease, while other PE species such as PE 34:2 was selected as indicative of being negative for COVID-19. Increased abundance of PE species was also recently reported by Ford et al in nasal swabs from COVID-19 positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies of circulating blood metabolites in COVID‐19 patients have yielded interesting biomarkers of infection, including hijacking of nucleic acid intermediates [ 20 , 21 , 22 , 23 ], dysregulation of lipid metabolism [ 22 , 24 , 25 ], changes in amino acid metabolism [ 23 , 25 ], alteration of energy metabolism [ 26 ], immune response [ 27 ], and indicators of hepatic cell damage [ 25 ]. However, a limitation of metabolomics alone is that it focuses on alterations of metabolites at a pathway level rather than identifying altered reaction/enzyme activity, which allows for more specific therapeutic targeting.…”
Section: Figmentioning
confidence: 99%
“…Studies with COVID-19 patients using untargeted or targeted metabolomics have consistently shown increased levels of glucose, free fatty acids, sphingomyelins and triglycerides, as well as changes in serum tryptophan metabolism [7][8][9][10][11][12] . As a result, various potential diagnostic and prognostic biomarkers have been proposed.…”
Section: Introductionmentioning
confidence: 99%